Penerapan Terapi Slimber Ice untuk Mengurangi Rasa Haus pada Pasien Gagal Ginjal Kronik yang Menjalani Hemodialisis - Margareta Ayu Mitasari; Novita Elisaebth Daeli; Sanny Frisca (Quantum Wellness : Jurnal Ilmu Kesehatan, 2025)
CKD patients undergoing hemodialysis need to manage fluid restrictions, fluid restrictions trigger thirst and cause hypervolemia which can worsen the patient's condition. The intervention of sucking ice cubes or slimmer ice can help reduce thirst and help patients manage fluids. The aim of this scientific work is to provide slimber ice therapy intervention to reduce thirst in Chronic Kidney Failure patients undergoing hemodialysis. This case study uses a descriptive method with a nursing process approach carried out on 3 respondents aged 19-56 years using a One Group Pretest Posttest research design and measured using the Visual Analog Scale (VAS) instrument before and after being given slimber ice therapy and analyzed by calculating the average value. The results showed that the age of the respondents was 19-56 years, gender was female for 1 respondent, male for 2 respondents. After being given slimber ice therapy to 3 respondents twice, when the patient underwent hemodialysis therapy twice a week, the average score for thirst was reduced from a VAS score of 5.1 (moderate thirst) to a score of 1.2 (light thirst) after being given the therapy. It is hoped that the results of this case study can be applied to reduce thirst and help limit fluids in CKD patients undergoing hemodialysis at Charitas Hospital Palembang.